The Involvement of TRIB3 and FABP1 and Their Potential Functions in the Dynamic Process of Gastric Cancer - Liu, Songyi; Ni, Chuxuan; Li, Yizhi; Yin, Honghao; Xing, Chengzhong; Yuan, Yuan; Gong, Yuehua (Frontiers in Molecular Biosciences, 2021)
Background: Dysregulated expression of TRIB3 and FABP1 have been previously observed in human cancer tissues. However, there are little information as to their expression change in dynamic gastric diseases and the functional roles. Methods: Tissues from a total of 479 patients, including 89 GS, 102 IM-GA, 144 EGC and 144 AGC were collected. The protein expressions of TRIB3 and FABP1 were detected by immunohistochemical staining. Meanwhile, the potential functions of TRIB3 and FABP1 in GC were further analyzed by R software and some internet public databases, such as TCGA and DAVID. Results: During this multi-stage process that go through GS to EGC, the expression trend of TRIB3 and FABP1 protein was GS > IM-GA > EGC. Besides, the expression of TRIB3 protein continued to decrease in AGC, while the expression of FABP1 was abnormally increased. Hp infection was significantly associated with the decreased expression of TRIB3 and FABP1. In addition, the diagnostic efficiency of the combination of these two indicators to diagnose EGC was higher than that of a single indicator. Survival analysis showed that higher expression of TRIB3 or FABP1 could indicate a better prognosis of GC. The protein expressions of TRIB3 and FABP1 were significantly positively correlated. Moreover, CEACAM5 and PRAP1 were positively correlated with both TRIB3 and FABP1 expressions, while GABRP and THBS4 were negatively correlated. The macrophages M0 infiltration was positively correlated with both TRIB3 and FABP1 expressions. Conclusion: The protein expressions of TRIB3 and FABP1 gradually decreased with the gastric disease progress, and was positively correlated. Hp infection may reduce the protein expression of TRIB3 and FABP1. Combing TRIB3 and FABP1 expressions can improve the diagnostic efficiency for EGC. Either a high expression of TRIB3 or FABP1 indicates a better prognosis for GC. TRIB3 and FABP1 may interact with CEACAM5, PRAP1, GABRP and THBS4, and affect tumor immune microenvironment by regulating immune cells, and participate in the development and progression of GC.